THE USE OF BIOTEXTILES TO RECUPERATE DEGRADADED AREAS BY EROSION - Marcia Silva Furtado; Neilianne de Fátima Costa Lima; Ulisses Denache Vieira Souza; Jane Karina Silva Mendonça; Antônio Teixeira Guerra; Antonio Cordeiro Feitosa (Sociedade & Natureza)
The erosion is a process that results from the conjunct action of many natural agents over the grounds. However, this process can be accelerated, mainly by the action of the human being that has caused numerous degrading actions of the environment, depending on the level of intensity and from the characteristic of his intervention. Among the ways of degradation it is possible to stand out accelerated erosive processes, like ravines and gullies.These processes can be mitigated with the use of several technical and material alternatives, being necessary specific knowledge for the right choice, in each case.In São Luís, a research project started since 2002 and thanks this project, it was indentified and monitorated several erosive processes with high degree of evolution, like gullies in Salina, Sacavém, Araçagi, Castelão, Bequimão, Coeduc, Santa Eulália site, among others.After these phases of the recognition and monitoration, the efforts for recuperation of the degraded areas have been developed with the use of bioengineering techniques. Such initiatives have been applied in different situations, with positive results for being an alternative which makes use of biodegradable materials such as vegetal fibers, wooden stakes, rigid iron-like structures, besides vegetation to make the soil more stable, lowering the costs and providing improvement to the environmental balance. Firstly, biodegradable screens, made of buriti, carnaúba, tucum, babaçu and marajá palm will be installed, as a matter of an experiment, at Sacavém’s gully, in São Luís – Maranhão State.The choice of the gullies in Sacavém occured because the necessity of the area, once this area offers serious risks to the population around, but later the project is going to contemplate the other monitored areas.